MicroRNAs – novel biomarkers for malignant pleural effusions - Wojczakowski, Wiktor; Kobylarek, Dominik; Lindner, Jacek; Limphaibool, Nattakarn; Kaczmarek, Mariusz (Contemporary Oncology/Współczesna Onkologia, 2019)
Lung cancer is one of the most common causes of cancer death. Its poor prognosis can be attributed to the patients’ advanced or metastatic presentation at the time of diagnosis. To improve and accelerate the diagnosis, better therapeutic and diagnostic methods are constantly being sought. MicroRNAs (miRNAs) are short nucleotide sequences of single-stranded, non-coding RNA that function as critical post-transcriptional regulators of gene expression. They are identified not only intracellularly, but also in physiological and pathological body fluids. These molecules are responsible for the regulation of approximately 33% of human genes, either regulating the expression of both oncogenes and suppressor genes or acting directly as an oncogene or suppressor gene itself. MiRNAs can contribute to the formation of cancer. The high specificity and sensitivity of miRNAs have been demonstrated with various malignant diseases, and for this reason, they raise particular interest as new and perspective biomarkers of tumours. Our work summarises the available information from recent years regarding the possibility of using miRNAs as biomarkers in the diagnosis of neoplasms. In this review, we focused on malignant pleural effusions with an emphasis on non-small cell lung cancer (NSCLC).